Fisheries Infrastructure Needs Analysis in Order to Capture Fisheries Development Based on Commodities of South Sumatra Province - Septifitri Septifitri; Daniel R Monintja; Sugeng Hari Wisudo; Sulaeman Martasuganda1 (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2010)
Development of capture fisheries in South Sumatra province in decline since the separation of Bangka Belitung province. This area of waters caused by the increasingly narrow. However, the development of fisheries sector still has a big opportunity, especially those based on competitive commodities. This study aimed to analyze the type of capture fisheries yield commodities, type, and allocation to take advantage of superior technology, excellent fish seumberdaya, and calculate the necessary facilities and infrastructure for the development of competitive commodities based fishery in South Sumatera province. Research conducted by survey with some analysis tools such as scoring methods, LGP and fishery facilities needs analysis. Flagship species of fish that can be developed such as prawn, swimming crab, fish and machete-cleaver manyung with superior fishing gear types trammel net, drift gill nets, gill nets and fishing equipment. Fisheries is needed is a means of fishery harbors as many as 10 pieces, as many as 20 fruit shipyards, factories nets one unit and processing 8 units. Addition of TPI as a necessary conclusion of the building where the sale of the landed catch of fishermen. Key Words : Capture Fisheries, Competitive Commodities, South Sumatera Province